2016
DOI: 10.1089/jmf.2014.0194
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Phytohemagglutinins from White Kidney Beans (Phaseolus vulgarisL., var. Beldia) in the Rat Small Intestine

Abstract: Although kidney bean (Phaseolus vulgaris L.) lectin toxicity is widely known, its effects in the gastrointestinal tract require further study. This investigation aimed to identify and characterize phytohemagglutinins (PHAs) in the small intestine and sera of rats following oral challenge with ground white beans. Twenty young, adult male rats were divided randomly into two groups of 10 animals each. The control group underwent gavage with a suspension of 300 mg of rodent pellet flour. The experimental group was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Since feces reported elsewhere were characterized upon their immuno-hemagglutination reactivities, it is very likely that the phytohemagglutinins (PHAs) were eliminated into the stools, but before day 10 (i.e., material collection day). Our preliminary immunobiochemical studies substantially evidenced the presence of bioactive PHAs in the jejunum and ileum of raw Beldia beans-fed rats [ 30 ]. However in the present study, no lectins were found in the feces and sera of animals on day 10 after 3 h of oral intubation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since feces reported elsewhere were characterized upon their immuno-hemagglutination reactivities, it is very likely that the phytohemagglutinins (PHAs) were eliminated into the stools, but before day 10 (i.e., material collection day). Our preliminary immunobiochemical studies substantially evidenced the presence of bioactive PHAs in the jejunum and ileum of raw Beldia beans-fed rats [ 30 ]. However in the present study, no lectins were found in the feces and sera of animals on day 10 after 3 h of oral intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Poor acceptability and digestibility, enzymes inhibitors (e.g., trypsin, chymotrypsin, and α-amylase), and lectins [ 71 ] could be responsible, but there is overwhelming evidence that the latter are at least one of the major causes. Since, an extensive mucosal hyperplasia was revealed along the jejunum and ileum of the rat small intestine [ 29 ], the damage noted on the disaccharidases activities could be attributed largely to the potent mitogens (i.e., growth factors); phytohemagglutinins (PHAs) [ 11 ], which were detected in immunologically intact form in the jejunal lumen, 3 h and 30 min after the orogastric gavage with BBFS [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nausea, vomiting, and diarrhea) in man [8]. It is generally believed that the lectins in P. vulgaris are the main causative agent responsible of these deleterious effects [9,10]. In this regard, some special attention should be given to the possible occurrence of bioactive lectins in human diets.…”
Section: Introductionmentioning
confidence: 99%
“…However, legume lectins are particularly resistant to cooking thus, improper cooking, as might occur in street vendered foods or foods cooked in the field, leave substantial amounts of active lectins in the food. It is often argued that legumes are cooked and since lectins are proteins, their biological activities are supposed to be eliminated, but this is not always true because residual lectins have been isolated in many cooked foods [21]. These residual lectins are reckoned as hazards, as they pose risks.…”
Section: Introductionmentioning
confidence: 99%